Flavonoid analyses and antimicrobial activity of various parts of Phaleria macrocarpa (Scheff.) Boerl fruit - Hendra, Rudi; Ahmad, Syahida; Md. Sukari, Mohd. Aspollah; Abd. Shukor, Mohd. Yunus; Oskoueian, Ehsan (MDPI AG, 2011)
Phaleria macrocarpa (Scheff.) Boerl (Thymelaceae) is commonly known as ‘Crown of God’, ‘Mahkota Dewa’, and ‘Pau’. It originates from Papua Island, Indonesia and it grows in tropical areas. Empirically, it is potent in treating the hypertensive,diabetic, cancer and diuretic patients. It has a long history of ethnopharmacological usage, and the lack of information about its biological activities led us to investigate the possible biological activities by characterisation of flavonoids and antimicrobial activity of various part of P. macrocarpa against pathogenic bacteria and fungi. The results showed that kaempferol, myricetin, naringin, and rutin were the major flavonoids present in the pericarp while naringin and quercetin were found in the mesocarp and seed. Furthermore, the antibacterial activity of different parts of P. macrocarpa fruit showed a weak ability to moderate antibacterial activity against pathogenic tested bacteria (inhibition range: 0.93–2.17 cm) at concentration of 0.3 mg/disc. The anti fungi activity was only found in seed extract against Aspergillus niger (1.87 cm) at concentration of 0.3 mg/well. From the results obtained, P. macrocarpa fruit could be considered as a natural antimicrobial source due to the presence of flavonoid compounds.